2008
DOI: 10.1109/tnn.2007.905840
|View full text |Cite
|
Sign up to set email alerts
|

Constrained Least Absolute Deviation Neural Networks

Abstract: It is well known that least absolute deviation (LAD) criterion or L 1 -norm used for estimation of parameters is characterized by robustness, i.e., the estimated parameters are totally resistant (insensitive) to large changes in the sampled data. This is an extremely useful feature, especially, when the sampled data are known to be contaminated by occasionally occurring outliers or by spiky noise. In our previous works, we have proposed the least absolute deviation neural network (LADNN) to solve unconstrained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…However, recent studies have shown that the disadvantages of TV-related artifacts can be mitigated by using least absolute deviation (LAD) data fidelity [16][17][18][19][20] as opposed to common ordinary least squares (OLS) data fidelity. A well characterized property of LAD is its robustness to outliers and sampling noise, and LAD has been applied to image interpolation [21], linear regression [22][23][24], neural networks [25], and the problem of regularized image restoration [22], but its application to MRI reconstruction requires further evaluation. It is worth noting that the integration of LAD and TV may generate an efficient algorithm for clinical purpose.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that the disadvantages of TV-related artifacts can be mitigated by using least absolute deviation (LAD) data fidelity [16][17][18][19][20] as opposed to common ordinary least squares (OLS) data fidelity. A well characterized property of LAD is its robustness to outliers and sampling noise, and LAD has been applied to image interpolation [21], linear regression [22][23][24], neural networks [25], and the problem of regularized image restoration [22], but its application to MRI reconstruction requires further evaluation. It is worth noting that the integration of LAD and TV may generate an efficient algorithm for clinical purpose.…”
Section: Introductionmentioning
confidence: 99%